Comparison between patients with norovirus‐related gastroenteritis and asymptomatic carriers with respect to distribution of antibody‐complexed viral particles and intestinal flora. Issue 12 (24th September 2018) - Mori, Kohji; Konishi, Noriko; Suzuki, Yasunori; Harada, Sachiko; Maeda, Masako; Akase, Satoru; Obata, Hiromi; Monma, Chie; Nagano, Miyuki; Kimoto, Kana; Oda, Mayuko; Somura, Yoshiko; et al.
Abstract : Asymptomatic carriers have a major influence on the spreading of norovirus infections. The objective of this study was to examine the characteristics of patients and asymptomatic carriers affected by norovirus‐related community gastroenteritis outbreaks. No significant difference between the two groups was observed in terms of the number of norovirus‐antibody complexes with respect to total numbers. Principal coordinates analysis of the intestinal flora based on β‐diversity analysis, revealed a different bacterial composition between patients and asymptomatic carriers, particularly regarding the genera Pseudomonas, Bacteroides, and Erwinia, as well as the Ruminococcaceae family. Although the proportional changes between these intestinal microorganisms were not sufficient to explain gastroenteritis symptoms, they represent possible markers shared by asymptomatic norovirus carriers.